Ethnography, ethnobiology and natural history: narratives on hunting and ecology of mammals among quilombolas from Southeast Brazil - Helbert Medeiros Prado; Raquel Costa da Silva; Marcelo Nivert Schlindwein; Rui Sérgio Sereni Murrieta (BMC, 2020)
Abstract Background As a leading practice of Homo sapiens' environmental experience for hundreds of millennia, hunting continues to evoke key research inquiries in the fields of archaeology, human ecology, and conservation biology. Broadly speaking, hunting has been mainly a subject of qualitative-symbolic and quantitative-materialistic schemata of analyze, among anthropologists and biologists, respectively. However, the phenomenological dimension of the hunting experience, in the course of individuals` everyday life, received little academic attention until this century. This study analyzes the daily praxis of hunting among quilombolas (descendants from runaway African slaves) in Southeast Brazil, making use of an ethnographic approach of phenomenological orientation, which dialogue with central ethnobiological issues. The authors also report the local ecological knowledge about mammals hunted in the area, and its relationship to the scientific literature on this subject. Methods Between 2016 and 2019, the authors made use of participant observation and informal interviews among eight key local participants, in three quilombola communities in the Ribeira Valley (São Paulo, Brazil). Fragments of authors' field notes and parts of interviewers' speeches make up the core results obtained. Results Articulating local knowledge to scientific literature, this study yielded a hybrid and comprehensive narrative about natural history of the mammals in the area. The authors also accessed elementary aspects of research participants' experience in hunting, such as strategies, tactics, motivations, and feelings. They reveal a set of human behavior dispositions that seems to emerge only in the context of the action, modulating the praxis of hunting on the course of individuals' everyday life. Conclusion Ethnography, ethnobiology, and natural sciences backgrounds were systematically articulated in this research. This made possible to get a contextualized and multifaceted understanding of hunting praxis in the Ribeira Valley, an important socioenvironmental context of Atlantic Forest in Brazil. The role of an ethnographic approach applied to ethnoecological and biological conservation issues is especially considered here.